New gel-like polymers as selective weak-base anion exchangers. - Błażej Gierczyk; Michał Cegłowski; Maciej Zalas (PLoS ONE, 2015)
A group of new anion exchangers, based on polyamine podands and of excellent ion-binding capacity, were synthesized. The materials were obtained in reactions between various poly(ethyleneamines) with glycidyl derivatives of cyclotetrasiloxane. The final polymeric, strongly cross-linked materials form gel-like solids. Their structures and interactions with anions adsorbed were studied by spectroscopic methods (CP-MAS NMR, FR-IR, UV-Vis). The sorption isotherms and kinetic parameters were determined for 29 anions. Materials studied show high ion capacity and selectivity towards some important anions, e.g., selenate(VI) or perrhenate.